Which Is The Most Offensively Powerful Starter Pokémon? - Codd, Thomas (Journal of Interdisciplinary Science Topics, 2017)
In the game of Pokémon, the player is initially given a starter Pokémon from their local Pokémon Professor. These Pokémon always either a fire type, a water type or a grass type. But which is the most powerful in its fully evolved form? Or rather, which of the fully evolved forms has the most powerful signature move? By analysing the anime and based on their signature moves, Charizard is the most powerful fully evolved original starter Pokémon by a considerable margin, and Blastoise is around twice as powerful as Venusaur.